Wall Shear Stress in Major Cerebral Arteries as a Function of Age and Gender—A Study of 301 Healthy Volunteers. Issue 3 (4th July 2014) - Zhao, Xixi; Zhao, Meide; Amin‐Hanjani, Sepideh; Du, Xinjian; Ruland, Sean; Charbel, Fady T.
ABSTRACT BACKGROUND The hemodynamic force of wall shear stress (WSS) has demonstrated a critical role in atherogenesis. PURPOSE To study the effect of age and gender on mean WSS (MWSS) values in major cerebral arteries. METHOD Thirteen cerebral arterial location sites in 301 healthy (157 M, 144 F; mean 47 ± 15 years; range 18‐84 years old) were studied. Quantitative magnetic resonance angiography was used to obtain volume flow and diameter, and subsequently to calculate MWSS via the Hagen‐Poiseuille equation. RESULTS MWSS decreased significantly with age in all vessels, declining from 9.5 to 5.7 dynes/cm2 in the neck vessels and from 22.9 to 16.2 dynes/cm2 in the intracranial vessels. MWSS is significantly higher in females than in males in all six neck vessels. The most significant drop in MWSS occurred between the age groups 48‐57 and 58‐67 (P < .05 for 12 vessels). CONCLUSION The overall decline in MWSS observed with age may be due to a decrease in flow. However, the marked drop in MWSS between the 48‐57 and 58‐67 age groups corresponded with an increase in diameter and systolic blood pressure rather than a significant drop in flow.